Applications of Novel Microscale and Nanoscale Materials for Theranostics: From Design to Clinical Translation - Mengxiang Tian; Bingzhi Dong; Weiqi Li; Liying Wang; Hong Yu (MDPI AG, 2024)
The growing global prevalence of chronic diseases has highlighted the limitations of conventional drug delivery methods, which often suffer from non-specific distribution, systemic toxicity, and poor bioavailability. Microscale and nanoscale materials have emerged as innovative solutions, offering enhanced targeting, controlled release, and the convergence of therapeutic and diagnostic functions, referred to as theranostics. This review explores the design principles, mechanisms of action, and clinical applications of various novel micro- and nanomaterials in diseases such as cancer, cardiovascular disorders, and infectious diseases. These materials enable real-time monitoring of therapeutic responses and facilitate precision medicine approaches. Additionally, this paper addresses the significant challenges hindering clinical translation, including biocompatibility, potential toxicity, and regulatory issues. Ongoing clinical trials demonstrate the potential of nanomaterials in theranostic applications, but further research is needed to overcome the barriers to widespread clinical adoption. This work aims to contribute to the acceleration of integrating nanomedicine into clinical practice, ultimately enhancing the efficacy and safety of therapeutic interventions.